Memahami Kristologi Menurut Kolose 1:28 Untuk Membina Jemaat Melalui Model Partners in Learning - Yustinus Hia (SCRIPTA: Jurnal Teologi dan Pelayanan Kontekstual, 2023)
The purpose of this journal is to apply the principles of fostering church members through the teaching model of partners in learning where coaches and congregations emphasize the importance of relationships to build trust between the two parties. As was done by the Lord Jesus Himself in His ministry, namely building relationships with the people He served, this partner in learning model also applies the importance of acceptance and appreciation between personal mentors and the congregation. Some of the impacts of the partners in Learning model: (1) Involvement means increasing the partnership between tutors and students, (2) Awareness. This model helps mentors and students to develop metacognitive awareness and a growing identity, (3) Improvement. Learners are more active and responsible for the learning program that is being carried out. Partners in learning change the way of 'telling students about topics they need to know' to facilitating them to get the necessary information (inquiry). Partners in learning will produce students like Paul taught in Col. 1:28 namely growing towards maturity towards Christ.